2011
DOI: 10.1111/j.1365-2656.2011.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

The nested assembly of individual-resource networks

Abstract: Summary1. Much of the current understanding of ecological systems is based on theory that does not explicitly take into account individual variation within natural populations. However, individuals may show substantial variation in resource use. This variation in turn may be translated into topological properties of networks that depict interactions among individuals and the food resources they consume (individual-resource networks). 2. Different models derived from optimal diet theory (ODT) predict highly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(156 citation statements)
references
References 48 publications
5
146
0
5
Order By: Relevance
“…Sometimes, individuals with a narrower diet feed on a subset of the items consumed by individuals with a broader diet, what could be interpreted as evidence of an optimal diet (Howell andHartl 1980, Pyke 1984), as the items in the population's diet could be ranked according to their cost-benefit relationship from preferred to occasional. The most important items would be present in the diets of most individuals, while the least consumed items would appear only in the diet of the most generalistic individuals (see, for instance, Pires et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, individuals with a narrower diet feed on a subset of the items consumed by individuals with a broader diet, what could be interpreted as evidence of an optimal diet (Howell andHartl 1980, Pyke 1984), as the items in the population's diet could be ranked according to their cost-benefit relationship from preferred to occasional. The most important items would be present in the diets of most individuals, while the least consumed items would appear only in the diet of the most generalistic individuals (see, for instance, Pires et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the use of network analysis can be a powerful tool to find out patterns of individual resource use [23], [35], [36], having the potential to elucidate which factors may promote different network topologies [34]. In this study, the assessment of the network-based inter-individual variation parameter is used as a starting point that may allow a subsequent in-depth analysis of the network properties.…”
Section: Introductionmentioning
confidence: 99%
“…A population would be organized in clusters when different groups of individuals specialize on different subsets of resources, in such a way that individuals within a group strongly compete with the rest of the members of that group, but show little competition with the individuals belonging to other clusters [34]. Nestedness, on its part, appears when individuals with both narrow (specialist individuals) and broad (generalist individuals) niches are found in a population, in such a way that the resources consumed by the specialists are ordered and predictable subsets of the resources used by the generalists [23], [35], [37]. Additionally, anti-nested patterns could emerge if the nestedness is lower than expected by chance [38], as happens in checkerboard patterns, in which pairs of prey species that never co-occur can be found [39].…”
Section: Introductionmentioning
confidence: 99%
“…5a, b). Like many other studies, at sites with greater conspecific density, individuals are forced to specialize on underutilized prey (Svanbäck and Bolnick 2005;Tinker et al 2012;Pires et al 2011). However, all the true frogs had a negative relationship between conspecific density and IS.…”
Section: !mentioning
confidence: 82%
“…Individuals can differ in their rank order of less preferred prey items or can have the same rank order of prey but differ in when they switch to those alternative prey types depending on the frequency of the top ranked prey (Svanbäck and Bolnick 2005). Network analysis has demonstrated that both types of expansion are possible in natural populations (Araújo et al 2008;Pires et al 2011;Tinker et al 2012). However, intraspecific competition may not always be a diversifying force.…”
Section: Figuresmentioning
confidence: 99%